Virtual tabletop games: features and capabilities - Harbuzova, D.; Kulishova, N. (ХНУРЕ, 2025)
This article explores virtual tabletops (VTTs) as interactive multimedia publications in tabletop role-playing games (TTRPGs). It analyzes how these digital platforms combine automation, interactivity, and immersive technologies to enhance gameplay. The study examines the role of 2D and 3D platforms, customization tools, and world-building mechanisms in shaping the digital game environment. Additionally, it examines VTT engine optimization for better performance and accessibility and their growing impact on the gaming industry.
Keywords: technologies; multimedia